Glutathione and related enzyme levels in the erythrocytes of chronic haemodialysis patients - (:unkn) unknown (My University, 1992)
[No abstract available]
Keywords: Erythrocyte; Glutathione; Glutathione peroxidase; Glutathione reductase; Glutathione transferase; Haemodialysis; Kidney